A Comparative Clinical Study on Vamana and Virechana Karma in the Management of Ekakushtha with Special Reference to Psoriasis (International Journal of Ayurveda and Pharma Research, 2021)
Ekakushtha is one of the Kshudra Kushtha described in Ayurvedic classics. It predominantly involves Vata and Kapha Dosha and characterized by Asvedanam (Anhidrosis), Mahavastu (large area of involvement), Matsyashakalopamam (scaling), Krishna Aruna Varna (black or reddish brown skin lesion), Kandu (itching) and Rukshata (dryness). In modern science it can be co-related with Psoriasis. According to W.H.O. the world wide prevalence of Psoriasis is 2-3% (April, 2013). In India prevalence of Psoriasis varies from 0.44 to 2.88%. Acharya Charaka mentioned that treatment of Ekakushtha is to be carried out according to involvement of excessive Dosha. It is Bahudosha (excessively aggravated Dosha) and Chirkari (chronic) Vyadhi (disease). In this condition Shodhana Chikitsa (purificatory measures) is best. So in this present study Vamana Karma and Virechana Karma is chosen for the treatment of Ekakushtha. Here 60 cases of Ekakushtha (Psoriasis) were divided into two groups. Group A (30 patients) were subjected to Vamana Karma. Group B (30 patients) were subjected to Virechana Karma. The statistical analysis reveals that Vamana Karma is statistically more significant in the management of Ekakushtha. Here both the therapies i.e. Vamana Karma and Virechana Karma were effective in the treatment of Ekakushtha. But Vamana Karma was more effective than Virechana Karma.